Evaluation of alternative sustainable ingredients for use in companion animal diets - Holt, Dalton Arnold (Kansas State University, 2022)
The pet food industry has a unique position in the food system as it largely relies on by-products or co-products from the human food systems for ingredient sourcing. Considering the substantial size of the pet food market, identifying alternative ingredients for use in the pet food industry that are sustainability sourced will be essential. The first objective of this work was to evaluate fermentation characteristics of alternative fiber ingredients using an in vitro canine fecal inoculum model. Organic matter disappearance (OMD) and postbiotic production were determined for apple pomace (AP), blueberry pomace (BP), cranberry pomace (CP), tomato pomace (TP), and pea fiber (PF) incubated with inoculum for 1, 3, 6, and 12 h at 39ºC. The OMD was similar (P>0.05; average of 18.5%) between treatments with no effect of time (P>0.05). Total VFA concentration was highest for AP (P<0.05), followed by TP, BP and PF, and lowest for CP (1.17, 0.75, average of 0.48, and 0.21 mmol*g⁻¹ of substrate, respectively). AP and TP had greater butyrate concentrations (average of 0.0476mmol*g⁻¹ of substrate) than all other treatments (0.0093 to 0.0344mmol*g⁻¹ of substrate). Overall, the fiber substrates evaluated were marginally to moderately fermentable when incubated for up to 12 h with canine fecal inoculum. The second objective was to evaluate the use of a yeast biomass as a novel protein source in feline diets. An extruded feline diet containing Torula yeast (TY) was evaluated for diet processing, palatability, and apparent total tract digestibility (ATTD) compared to diets containing pea protein (PP), soybean meal (SM), and chicken meal (CM). During diet production, specific mechanical energy of TY and SM (average of 187 kJ/kg) was greater (P<0.05) than for PP (138 kJ/kg) but not different (P>0.05) from CM (167 kJ/kg). Kibble sectional expansion and piece volume were greatest for TY (P<0.05). Cats fed TY had greater intake ratios (P<0.05) than CM and PP (0.88 and 0.73, respectively), but were not different (P>0.05) from SM. ATTD of dry matter (DM), organic matter (OM), and gross energy (GE) was greater (P<0.05) for CM (87.43, 91.34, 90.97%, respectively) than TY. The ATTD of DM, OM, and GE was similar (P<0.05) for TY to PP and SM (averages of 86.20, 89.76, and 90.22%, respectively). Crude protein ATTD of TY was similar to other treatments (average of 89.97%), but fat ATTD was lower (P<0.05; 92.52%) than other treatments (93.76 to 94.82%). Total dietary fiber ATTD was similar between TY and CM (average of 66.20%) and greater (P<0.05) than PP and SM (average of 58.70%). In summary, the Torula yeast facilitated kibble formation, increased diet preference, and was highly digestible when fed to cats. The results here provide valuable data on the use of high-fiber food processing by-products and yeast derived proteins in companion animal diets. Alternative ingredients, such as these, have great potential to provide valuable, sustainably sourced ingredients for pet diets.
Keywords: Companion animals; Torula yeast; Pet food; In vitro fermentation; Fiber; Alternative protein